Intercultural church : a biblical vision for an age of migration - Marzouk, Safwat, 1978- (Word & world books., 2019)
Safwat Marzouk offers a biblical vision for what it means to be an intercultural church, one that fosters just diversity, integrates different cultural articulations of faith and worship, and embodies an alternative to the politics of assimilation and segregation. A church that fosters intercultural identity learns how to embrace and celebrate difference, which in turn enriches its worship and ministry. While the church in North America might see migration as an opportunity to serve God's kingdom by showing hospitality to the migrant and the alien, migration offers the church an opportunity to renew itself by rediscovering the biblical vision of the church as a diverse community. This biblical vision views cultural, linguistic, racial, and ethnic differences as gifts from God that can enrich the church's worship, deepen the sense of fellowship in the church, and broaden the church's witness to God's reconciling mission in the world. Today's church faces the challenge of what it means to be church in the light of the ever-growing diversity of the population. This may entail advocacy work on behalf of the undocumented, asylum seekers, and refugees, but the church also faces the question of how to welcome the stranger, the migrant, and the refugee into the heart of the worshipping community. This may mean changing worship, leadership, or ministry styles to embrace diverse communities in the church's neighborhood. Marzouk surveys numerous biblical texts from the early ancestor stories of Israel to the Prophets, to the Gospels and Acts, the letters of Paul, and Revelation. The stories introduce themes of welcoming strangers, living as aliens, playing host to outsiders, discovering true worship, and seeking common language for expressing faith. Discussion questions are provided to encourage conversation on this complex and important topic.